UNRAVELING THE ROLE OF EXCHANGE RATES: BRIDGING GOLD AND OIL PRICES TO INDONESIA’S SHARIA STOCK INDEX - Mulatsih, Srie Nuning; Septiani, Ulfa (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study analyzes the factors influencing the Sharia Stock Index in Indonesia based on world gold prices, crude oil prices, and BI Rate. Furthermore, to observe more complex conditions, the exchange rate was included as a form of mediation. The data in this study are time-series data collected from May 2011 to December 2023. The data were analyzed using time-series data regression, which involved mediating variables. The results show that world gold prices, crude oil prices, and the BI rate significantly affect the Indonesian Sharia Stock Index. The exchange rate mediates the effect of gold and crude oil prices on the Indonesian Sharia Stock Index but does not mediate the BI rate. This finding implies that the dynamics of global commodity prices and exchange rates should be the primary consideration in the investment strategy for Sharia stocks in Indonesia. In addition, the influence of the BI rate shows that the role of domestic monetary policy has also been proven to be significant in influencing the movement of the index.